Mindfulness-based Therapeutic Sailing for Veterans With Psychiatric and Substance Use Disorders. Issue 3 (10th February 2021) - Marchand, William R; Klinger, William; Block, Ken; VerMerris, Scott; Nazarenko, Elena; Curtis, Heather; Newton, Julie; Herrmann, Tracy S; Yabko, Brandon; Lane, Jose
ABSTRACT: Introduction: Complementary interventions have the potential to enhance treatment engagement and/or response among veterans with psychiatric disorders and/or substance use disorders (SUDs). Mindfulness-based therapeutic sailing (MBTS) is a novel three-session, complementary intervention, which combines nature exposure via recreational sailing and mindfulness training. It was developed specifically to augment both treatment response and engagement among veterans with psychiatric disorders or SUDs. The study reports a follow-up investigation of a version of MBTS modified based upon a previous initial pilot study. Materials and Methods: This is an institutional review board–approved study of 25 veterans, 23 males and 2 females, who participated in MBTS along with a diagnosis-, gender-, and age-matched control group. All participants had at least one psychiatric disorder or SUD and most (92%) had two or more conditions, with the most common being any SUD (76%) and PTSD (72%). Instruments used to evaluate within-subjects pre- to post-intervention psychological changes were the Acceptance and Action Questionnaire II (AAQII), the Toronto Mindfulness Scale (TMS), and the Five Facet Mindfulness Questionnaire (FFMQ). The Physical Activity Enjoyment Scale (PACES) was administered to evaluate how much the participants enjoyed the intervention. Outcome measures were collected for 1-year pre-intervention and 1-year post-intervention for between-subject analyses. These were numbers of medical and psychiatric hospitalizations, emergency department visits, mental health (MH) and substance abuse treatment visits, and MH and substance abuse treatment failed appointments. Data analysis consisted of using paired, two-tailed t -tests on psychological instrument results, Poisson regression on discrete outcome measures, and chi-square test of independence on demographic factors. Results: Within-subjects comparisons revealed significant mean pre- to post-intervention increases in AAQII ( P = .04) and TMS scores ( P = .009). The FFMQ scores increased but the change was nonsignificant ( P = .12). The PACES scores were high for all sessions, indicating enjoyment of the intervention by participants. Although the coefficient was nonsignificant, Poisson regression uncovered reduction in substance abuse treatment visits post-intervention. There were no significant differences for the other variables. For demographic factors, the differences between intervention and control groups were not statistically significant. Conclusions: The MBTS is associated with increases in psychological flexibility (AAQII) and state mindfulness (TMS). The intervention was perceived as pleasurable by participants (PACES) and is potentially associated with decreased utilization of substance use treatment services. These results must be considered as preliminary; however, these finding corroborate results from a previous pilot study and indicate that MBTS holds promise as a complementary intervention that could result in enhanced treatment engagement and/or outcomes for the population studied. A randomized controlled trial of MBTS is warranted. Further, the model of a three-session intervention combining mindfulness training with nature exposure could be adapted for other types of nature exposure, such as hiking or snowshoeing or other complementary interventions including equine-assisted activities and therapies.